Prevalence and Baseline Clinical Characteristics of Eosinophilic Chronic Obstructive Pulmonary Disease: A Meta-Analysis and Systematic Review - Wu, Hong-Xia; Zhuo, Kai-Quan; Cheng, De-Yun (Frontiers in Medicine, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease, with different clinical and pathophysiological characteristics. Accumulative evidences show that eosinophil levels may be connected to therapy effect and phenotypes of COPD. However, the prevalence of eosinophilic inflammation in COPD and the baseline characteristics of eosinophilic COPD remain unknown. Our study investigated the prevalence of eosinophil >2% among COPD and characteristics of eosinophilic COPD. Methods We searched Cochrane Central Library, Medline, Embase, Web of Science for trials of eosinophil and COPD, published from database inception to May 1, 2019. Results: A sum of 40,112 COPD patients were involved in nineteen trials in the final analysis. The prevalence of eosinophilic COPD was range from 18.84% to 66.88%, and 54.95% on the whole. We found higher rate of male, ex-smoker and ischemic heart disease (OR 1.36, 95%CI 1.26–1.46, P<0.00001; OR 1.23, 1.12–1.34, P<0.0001; OR 1.31, 1.14–1.50, P=0.001), lager BMI (MD 0.70, 0.27–1.12, P=0.001), but lower proportion of GOLD stage I in eosinophilic COPD (OR 0.84, 0.73–0.96, P=0.01). No significant difference was found in age, current-smoker, pack-years smoked, percent of predicted forced expiratory volume in 1s (FEV1), hypertension, diabetes, and others GOLD stage between two groups (P >0.05). Conclusions: Our analysis suggested that eosinophilic inflammation is prevalent in COPD. Eosinophilic COPD was prone to male, ex-smoker, lager BMI and high risk of some comorbidity, but had low proportion of mild airflow limitation patients.